HEAVY METALS IN SURFACE SEAWATER AND SEDIMENT FROM THE COAST OF KHANH HOA PROVINCE: LEVELS AND ECOLOGICAL RISK ASSESSMENT - Xuan Thuy Nguyen; Nhat Nhu Thuy Nguyen; Hung Phu Le; Trong Dung Le; Viet Ha Dao; Xuan Vy Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Contamination by heavy metals in coastal and marine environments is an increasingly serious threat to both marine ecosystems and humans. The numerous marine cultivation and industrial zones along the coast of Khanh Hoa may influence the heavy metal contamination in the seawater and marine sediments. In this study, 36 seawater and 36 marine sediment samples were collected along the coast of Khanh Hoa to evaluate the levels of eight heavy metal elements. The results indicated that heavy metal concentrations in the surface seawater at Khanh Hoa were much lower than the national technical regulatory limits. The comprehensive pollution index of the heavy metals averaged less than 1. Therefore, heavy metal pollution in the seawater along the coast of Khanh Hoa is slight. Among the eight heavy metals (Cd, Co, Cu, Cr, Mn, Ni, Pb, and Zn) analyzed in the sediments, Cu concentration in the sediment at Cam Ranh Bay is much higher than the national technical regulatory limit. Ecological risk assessment of the sediments also indicated a possible combined biological effect of Cu, Pb, and Zn at Cam Ranh. Therefore, heavy metals in the marine environment at Khanh Hoa should be monitored yearly. Decision-makers should consider the Cu content in seafood because bioaccumulation of heavy metals may occur in marine organisms.